Puya vallis-colcaensis (Bromeliaceae) a new species from the Peruvian Andes - Treviño-Zevallos, Italo F.; Gouda, Eric J.; Quipuscoa, Victor; Bravo, Cinthia (Phytotaxa, 2025)
A new Puya species, Puya vallis-colcaensis (Bromeliaceae, Puyopsis), that inhabits the high Andean region of Arequipa in southern Peru, is described and illustrated. This species has greenish-black petals, a compound inflorescence with branches measuring 11–15 cm long, floral bracts that turn dark when dry, and sepals with dense stellate trichomes, carinate toward the apex. This species was locally mistaken for the similar P. weberbaueri, but a comparative and detailed analysis of its morphology reveals that it should be considered a new taxon.